1974
DOI: 10.2527/jas1974.384758x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Calcium and Phosphorus Level upon Calcium, Phosphorus and Nitrogen Balance in Swine

Abstract: Three metabolism trials were conducted to determine the effects of dietary calcium and phosphorus level upon calcium, phosphorus and nitrogen balance in growing swine. The nine pigs in each trial averaged 22.6, 25.2 and 26.5 kg initially for trials 1, 2 and 3, respectively. The diets contained three levels of calcium and three levels of phosphorus and were rotated among the pigs in the three trials. Feed intake was adjusted to metabolic size.Within the limits of the calcium and phosphorus levels used in this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
34
0
4

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 13 publications
11
34
0
4
Order By: Relevance
“…This would also affect the amount of P excretion. Similar effect was found in an earlier study by Vipperman et al (1974), where a significant interaction between calcium and P was observed for P digestibility and retention.In the current version of the model, the missing interaction between Ca and P retention limits the use of the model when applied with diets that are limiting in Ca. This limitation is also demonstrated by some of the comparisons with experimental data presented in the companion paper (Symeou et al, 2014).…”
supporting
confidence: 76%
“…This would also affect the amount of P excretion. Similar effect was found in an earlier study by Vipperman et al (1974), where a significant interaction between calcium and P was observed for P digestibility and retention.In the current version of the model, the missing interaction between Ca and P retention limits the use of the model when applied with diets that are limiting in Ca. This limitation is also demonstrated by some of the comparisons with experimental data presented in the companion paper (Symeou et al, 2014).…”
supporting
confidence: 76%
“…Assim, quando o nível de absorção do P não atende às exigências metabólicas, o P reciclado do osso aumenta e o excesso pode ser detectado no plasma, motivo pelo qual alguns pesquisadores consideram esta variável um indicador pouco preciso do aproveitamento do P (Vipperman Jr. et al, 1974).…”
Section: Resultsunclassified
“…Os valores do P retido revelam relação linear positiva entre a retenção (Y) e o consumo de P (X), expressa pela equação: Ŷ = -23,706 + 0,615X; R 2 =0,8876, P<0,01, o que está de acordo com o observado por MUDD et al (1969) e VIPPERMAN JR. et al (1974, em dietas de leitões em crescimento, com o P variando entre 0,38 e 1,47% e 0,25 e 0,75%, respectivamente.…”
Section: Lopes Et Alunclassified
“…Este valor é praticamente o mesmo obtido, levando em consideração técnica da diluição isotópica para avaliação das perdas endógenas (38,58 mg P/kg peso/dia), o que reforça o balanço de P, como importante indicativo Tabela 2 -Valores das variáveis em função das dietas experimentais Plasm P na determinação da exigência deste mineral para suínos. Com relação à absorção de P, observou-se resposta linear positiva com o consumo deste mineral, equação: Ŷ = -35,925 + 0,7888X; R 2 =0,9472; P<0,01, o que está de acordo com os resultados observados nos trabalhos de MILLER et al (1964), VIPPERMAN JR., et al (1974), BELLAVER et al (1983) e FERNANDEZ (1995a. Já o coeficiente de absorção do P apresentou resposta quadrática ao consumo de P equação: Ŷ = -0,1068 + 0,0064X -0,000013X 2 ; R 2 =0,70; P<0,01.…”
Section: Lopes Et Alunclassified